Rewriting the Reich: German Women Journalists as Transnational Mediators for Germany's Rehabilitation - Barton, Deborah (Central European History, 2018)
This article looks at the transnational impact of two diaries written by the female German journalists Ruth Andreas-Friedrich and Ursula von Kardorff, whose journals shed light on German wartime experiences, resistance activities, and, to a lesser extent, the press. In the postwar years, both journalists sought to influence (West) Germany's relationship with its former enemies, in particular the United States. In their autobiographical writing, they presented both an image of Germany as a victim of Nazism, as well as an early acknowledgment of German crimes. In this way, they achieved a balanced narrative that received a positive reception from American and German audiences. Though the ways in which Friedrich and Kardorff presented aspects of journalism and everyday life in the Third Reich were not unique, their dual identity as women and journalists underlay their ability to act as “legitimate” mediators for Germany's rehabilitation. Western allied occupation authorities and overseas audiences viewed them, in contrast to men, as largely apolitical because they were women, and as objective witnesses because they were journalists. Through their autobiographical writings, both journalists situated themselves among the predominantly male US and German elites devoted to developing amicable relations between the two countries via soft-power diplomacy., Dieser Aufsatz untersucht die transnationalen Auswirkungen zweier Tagebücher, die der beiden deutschen Journalistinnen Ruth Andreas-Friedrich und Ursula von Kardorff. Die Tagebücher sind auch im Hinblick auf deutsche Kriegserfahrungen, Widerstandsaktivitäten und – in geringerem Ausmaß – die Presse aufschlussreich. Beide Journalistinnen versuchten in den Nachkriegsjahren das westdeutsche Verhältnis zu dessen ehemaligen Feinden, insbesondere den Vereinigten Staaten, zu beeinflussen. In ihren autobiographischen Schriften präsentierten sie ein Bild von Deutschland, das selbst Opfer des Nationalsozialismus war, lieferten aber gleichzeitig ein frühes Eingeständnis der deutschen Verbrechen. Dadurch erreichten beide eine ausgewogene Schilderung, die sowohl vom amerikanischen als auch vom deutschen Publikum positiv aufgenommen wurde. Obwohl das, was Friedrich und Kardorff über die Facetten von Journalismus und Alltag im Dritten Reich zu sagen hatten, nicht einzigartig war, trug ihre doppelte Identität als Frauen und Journalistinnen dazu bei, dass man sie als „legitime“ Mediatoren der Rehabilitation Deutschlands ansah. Die westlichen Besatzungsbehörden und Leser in Übersee betrachteten die beiden im Gegensatz zu Männern als weitgehend apolitisch, weil sie Frauen waren, und als objektive Zeitzeugen, weil sie Journalistinnen waren. Durch ihre autobiographischen Schriften konnten sich die beiden Journalistinnen unter den überwiegend männlichen US-amerikanischen und deutschen Eliten etablieren, die mit Hilfe von soft-power Diplomatie freundschaftliche Beziehungen zwischen den beiden Ländern fördern wollten.